Pengaruh Komitmen Organisasional, Lingkungan Kerja, Prestasi Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Perkebunan Nusantara IV Kebun Ajamu - Nst, Rizki Syahputra; Syahmewah, Rika (Jurnal Manajemen Akuntansi (JUMSI), 2024)
In the midst of today's competitive challenges, the company strives to achieve its goals. One of the strategies implemented is to have a workforce that shows superior performance. According to Mondy (2010), performance refers to a goal-focused process, aimed at ensuring that the organizational structure is optimal in order to increase the productivity of employees, teams, and overall, the organization. PT Perkebunan Nusantara IV, or PTPN IV, is one of the companies owned by the government. They focus on plantation, processing, and marketing of plantation products. PTPN IV manages rubber and oil palm plantations. Their main products are palm kernel oil and palm oil (Radian, 2012).Employee competency development: PTPN IV regularly organizes training and development programs to improve the technical expertise and managerial abilities of employees. This has an impact on increasing productivity and quality of work.